Substitution of Chemical Fertilization using PGRs Evident in Growth and Yield of Tomato (Journal of Science and Technology Research, 2024)
The excessive utilization of synthetic fertilizers and chemicals poses a significant threat to both environment and human well-being. A pot experiment was done between December 2022 and April 2023 using a factorial randomized complete block design, which involved combining fertilizers and plant growth regulators (PGRs). The objective was to decrease the utilization of artificial fertilizers through the application of PGRs. The experiment involved applying fertilizers at 80, 90, 100 and 110% of the recommended doses. The recommended doses consist of 12 grams (g) of urea, 10 g of TSP, 5 g of MoP, 3 g of gypsum, 0.5 g of zinc sulphate, and 0.5 g of boric acid per plant. Furthermore, PGRs including gibberellic acid (GA3), naphthalene acetic acid (NAA), 4-chlorophenoxy acetic acid (4-CPA), and salicylic acid (SA) were applied at a concentration of 50 ppm. The results showed that there were no significant differences in growth and yield-contributing features when the fertilizer dose was increased from 80% to 110% of the recommended amount. Nonetheless, there were significant differences compared to the control group. However, PGRs showed significant variability in the morphological and reproductive responses of tomatoes under the conditions being researched. The GA3 treatment resulted in significantly greater plant height, base diameter, number of branches and leaves per plant, canopy spread, and internode length. Moreover, GA3 at 50 ppm produced the highest number of flowers and fruits/plant, with a single fruit weighing 67.83 g and a total fruit production of 6.61 kg/plant of tomato. Among the other PGRs, salicylic acid showed statistical equivalence to GA3 treatment. Nonetheless, there was a notable decrease in both vegetative and reproductive features, including yield, when NAA and 4-CPA were used. The interaction between fertilizers and PGRs showed that combining GA3 and SA with any of the tested fertilizer rates resulted in statistically distinct and improved vegetative and reproductive responses. However, the combination of fertilizer with NAA and 4-CPA produced highly unsatisfactory outcomes. Therefore, GA3 at 50 ppm and SA at 50 ppm can effectively be employed as substitute of synthetic chemical fertilizers in tomato cultivation.J. of Sci. and Tech. Res. 6(1): 53-64, 2024